Attitudes towards technology among distance education students: Validation of an explanatory model - Romero Martínez, Sonia J.; Ordóñez-Camacho, Xavier G.; Guillen-Gamez, Francisco David; Bravo Agapito, Javier (Online Learning, 2020)
Attitudes towards technology are preconceived notions that have an effect on the teaching-learning process and on the academic-professional performance of students, in particular those who use technology as a means of study. This investigation has two objectives: on the one hand, to test the measuring properties (reliability, factorial structure) of an instrument to measure attitudes and, on the other hand, to propose and validate a model that hypothesizes that digital competence and frequency of use of technologies have a positive impact on same. 1251 students of the Madrid Open University participated. It is a non-experimental, explanatory study using structural equation methodology. The results show adequate psychometric properties for the test and good adjustment of the proposed model (χ²=163.91, df=37, p<.001) allowing for further exploration of the relationship between use, skill and attitudes in the distance education context and improving the properties of measuring instruments proposed in Spanish.